Politics of Prophecy in Java: A Mythological Narrative on Political Succession of Javanese Dynasties in Babad Tanah Jawi - Achmad Fawaid; Wening Udasmoro; Sri Margana (Khazanah Sosial, 2022)
This article is to figure out how Javanese power succession has archetypal structures and relational systems in Babad Tanah Jawi, representing that the past is prophetic prologomena for the future. Using LÃ©vi-Straussâ€™s structural anthropology of myth as a methodological approach, this study attempts to analyze the relational systems of successive power of Javanese characters (rulers) from pre-Majapahit to early Mataram in Babad Tanah Jawi and to interpret symbols of the prophetic divine during the periods of different Javanese reigns. This study has found that Javanese dynastic succession has been characterized by archetypal structures, in which the Javanese rulers commonly passed through identical phases of life-journeys, ranging from getting divination from fortune-teller (prophecy), getting out of the origins (exodus), to getting political recognition to be the next ruler (legitimacy). This system argues that the mythological prophecy in Babad Tanah Jawi is political because it prevails the logic of the Javanese worldview (weltanschauung) and the precondition of mystical and political legitimacy for Javanese rulers. The narratives of prophetic symbols, in which the different Javanese rulers had been involved in similar forms and structures, also imply the political dimension of prophecy representing the power of their reigns.